Price and Location Analysis Of Housing Buying Decisions in The Buru Project Perumnas - Muspiha Muspiha; Masna Hatuwe (Lembaga Jurnal dan Publikasi Universitas Muhammadiyah Buton, 2023)
Based on the description of the background above, the authors formulate the problem, namely a) Does the price affect the purchasing decision of the Buru Project Perumnas in the city of Namlea? and b) Does the location affect the purchasing decision of the Buru Project Housing Housing in Namlea City?. The research location in this writing is located in Namlea, the object of this research is the one occupying the Buru Project housing complex. Meanwhile, the research time the writer used to obtain the required data was 2 (two) months long. There are two sources of data, namely primary data and secondary data. The primary data source in this study is data obtained directly from the people living in the Buru National Housing Project. The data collection method, namely the interview method, is a way to obtain data by conducting direct interviews with respondents and leaders in order to obtain valid and reliable data. Furthermore, using the Questionnaire is a list of written questions that have been prepared beforehand. The population is a generalization area consisting of objects/subjects that have certain qualities and characteristics that are applied by researchers to be studied and then drawn conclusions.